A produção de paráfrases para a ampliação vocabular - Guimarães, Dayse Cardoso (2015)
In this study, we investigate the relevance of paraphrases production inserted in didactic sequences in the processes of teaching and learning of words, considering the presupposition that there is close relationship between the difficulties of expression and the vocabulary of the students. With this proposal of educational intervention developed in the Professional Master s Degree in Language and Literature at Universidade Federal de Uberlândia (PROFLETRAS-UFU), we aim to contribute to the expansion of lexical knowledge of students from elementary school. Considering the theoretical concepts adopted in this work, as the perspective of Fuchs (1982, 1985), we understand the paraphrase as a reformulation strategy whereby the author articulates lexical-semantic knowledge to contextual aspects in the construction of an equivalence relation among texts in a given communicative situation. Thus, due to lexical selection revealed in the produced paraphrases, the analysis of these ones gives an opportunity of more appropriate and relevant lexical reflections to the target audience of vocabulary teaching. Methodologically, the paraphrastic production for vocabulary teaching theory supported by Bezerra (2004), Leffa (2000), Meserani (2002), Ilari (2006), Gonçalves (1977), Dolz, Noverraz and Schneuwly (2004), among other specialists, is inserted in a didactic sequence that comprises: attentive observation and manipulation of lexical items from the reading of texts and the production of written paraphrases; and performing modules activities in order to confer constancy to lexical reflection and to the use of lexical units that are the teaching focus. Written paraphrases and other activities solved by the students are data for the effectiveness analysis of the applied work, which results prove the validity of paraphrases production in the development of vocabulary education and the expansion of lexical knowledge of the students, after an intentional teaching of words organized in didactic sequences. In addition, we conclude that the explicit teaching of lexical units is viable and productive, structured in teaching sequences, with a view to the production and the analysis of written paraphrases.